2021
DOI: 10.18502/fid.v17i34.5198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Casein Phosphopeptide Amorphous Calcium Phosphate Conditioning on Microtensile Bond Strength of Three Adhesive Systems to Deep Dentin

Abstract: Objectives: This study aimed to assess the effect of casein phosphopeptide amorphous calcium phosphate (CPP-ACP) on microtensile bond strength of three adhesive systems to deep dentin. Materials and Methods: In this in vitro study, the occlusal surface of 30 sound human third molars was sectioned at 2 mm below and above the cementoenamel junction. The samples were randomly divided into three groups of OptiBond Solo Plus, G-Bond, and Clearfil SE Bond. Before composite resin bonding, each group was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Out of the 13 studies included, two studies (15.4%) presented with a low risk of bias; nine studies (69.2%) presented a medium risk of bias, whereas the remaining two studies (15.4%) presented with a high risk of bias (Table 3). [12][13][14][15][16][17][18][19][20][21][22][23][24] None of the studies mentioned sample size estimation. Only two studies had mentioned about single operator carrying out all the experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 13 studies included, two studies (15.4%) presented with a low risk of bias; nine studies (69.2%) presented a medium risk of bias, whereas the remaining two studies (15.4%) presented with a high risk of bias (Table 3). [12][13][14][15][16][17][18][19][20][21][22][23][24] None of the studies mentioned sample size estimation. Only two studies had mentioned about single operator carrying out all the experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies measured shear bond strength (SBS), eight studies measured tensile bond strength, and only one research discussed the interfaces between resin and dentin have been studied using field-emission scanning electron microscopes (FE-SEMs). [13][14][15][16][17][18][19][20][21][22][23][24] According to the results of the study by Barbosa-Martins et al, 16 pretreating demineralized dentin with remineralizing materials has been shown to be an effective, workable way to improve bonding while according to Doozandeh and Mirmohammadi 12 etching dentin affected by caries for up to 45 seconds could improve its SBS and bring it almost to that of normal dentin (ND). Pretreatment with MI Paste™ did not significantly affect the SBS of the etch-and-rinse adhesive in CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation